Constructivism and Its Perspectives Related to Teaching And Learning Process In The Classroom : A Conceptual Framework - Welly Ardiansyah; Murwani Ujihanti (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2017)
Constructivism is a view that emphasizes the active role of students in building understanding and making sense of the information. The constructivist teaching is learner centered where students are actively involved in knowledge construction rather than mere passive listeners. Constructivists‟ views can be organized in two forms: psychological and social. In constructivists‟ view such as Piaget, students construct knowledge by transforming, organizing, reorganizing previous knowledge whereas in social constructivists‟ view such as Vygotsky, opportunities are provided to students to learn through social interaction in construction of knowledge and understanding. The paper is an attempt toexamine constructivist teaching and learning by providing in-depth analysis of features of constructivist theory and its two forms (psychological and social) and the organization of a constructivist classroom.